Health care provider's perceptions of factors that influence infant mortality in Papua Indonesia: A qualitative study. Issue 2 (March 2022) - Situmorang, Hotnida Erlin; Sweet, Linda; Graham, Kristen; Grant, Julian
Abstract: Background: High infant mortality remains a global health problem, particularly in less developed countries. Indonesia has one of the highest infant mortality rates in Southeast Asia. Known factors relate to documented medical conditions and do not necessarily explain their origin. Aim: To identify and explore factors that contribute to infant mortality in Papua, Indonesia, through the lens of health workers' perceptions. Methods: A qualitative descriptive approach using semi-structured interviews was used. Twelve Indonesian health workers participated. Interviews were audio-recorded and transcribed, and then analysed thematically. Findings: Five main themes were generated: beliefs and practices related to pregnancy, birth, and infants; infant health factors; maternal health factors; barriers to seeking, receiving and providing infant health care; and enablers and strategies for improving infant health. Discussion: Cultural factors were perceived as contributing to poor health outcomes by shaping decisions, help seeking behaviour and health care access. Poverty, health literacy, road access and transport, shortage of health staffing, and health equipment and medicines exacerbate poor health outcomes. Conclusion: Cultural knowledge and sensitivity are central to the provision and acceptance of health care by local families in Papua, Indonesia. Recommendations include: improving cultural sensitivity and cultural safety of service; implementing community health promotion to enhance maternal and infant health; improving community participation in health care planning and delivery; and enhancing collaboration between national, provincial, regency and local governments.